2012
DOI: 10.1099/ijs.0.027375-0
|View full text |Cite
|
Sign up to set email alerts
|

Ruminococcus champanellensis sp. nov., a cellulose-degrading bacterium from human gut microbiota

Abstract: A strictly anaerobic, cellulolytic strain, designated 18P13 T , was isolated from a human faecal sample. Cells were Gram-positive non-motile cocci. Strain 18P13 T was able to degrade microcrystalline cellulose but the utilization of soluble sugars was restricted to cellobiose. Acetate and succinate were the major end products of cellulose and cellobiose fermentation. 16S rRNA gene sequence analysis revealed that the isolate belonged to the genus Ruminococcus of the family Ruminococcaceae. The closest phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 23 publications
3
101
0
1
Order By: Relevance
“…the Ruminococcus species within the Lachnospiraceae ) to avoid confusion in the literature. The topology of our phylogenetic analyses also matches partial phylogenetic analyses performed for recently described species (Chassard et al , 2012; Wegmann et al , 2014) and offers some insights. For example, R. bromii appears less related to all other true ruminococci, as determined in our pairwise 16S rRNA similarity comparisons (88–89 % 16S identity; Table S8).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…the Ruminococcus species within the Lachnospiraceae ) to avoid confusion in the literature. The topology of our phylogenetic analyses also matches partial phylogenetic analyses performed for recently described species (Chassard et al , 2012; Wegmann et al , 2014) and offers some insights. For example, R. bromii appears less related to all other true ruminococci, as determined in our pairwise 16S rRNA similarity comparisons (88–89 % 16S identity; Table S8).…”
Section: Discussionsupporting
confidence: 76%
“…Some species are cellulolytic, including the rumen isolates R. flavefaciens and Ruminococcus albus (Hungate, 1957), and the recently described human isolate Ruminococcus champanellensis (Chassard et al , 2012), which is the only known bacterial species isolated from the human colon capable of degrading crystalline cellulose (Moraïs et al , 2016). Others are non-cellulolytic and utilize polysaccharides like resistant starches in the case of R. bromii (Ze et al , 2012), or selectively use various plant hemicelluloses in the case of Ruminococcus callidus (Lay et al , 2005) and ‘ Ruminococcus bicirculans ’ (Wegmann et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The T-RF 168 bp (OTU04) was only observed in the digester operating at 44°C (R 44 SS). This clone was most closely related to Ruminococcus champanellensis (61.8% identity), a cellulolytic bacterium isolated from human faeces that ferments cellulose, cellobiose and xylan, produces acetate and succinate as the main fermentation products and grows optimally from 33°C to 39°C (optimum 39°C) [41]. In a previous study, the abundance of Ruminococcus in a biogas digester was shown to increase after pre-treatment of sludge from a wastewater plant [32].…”
Section: Cel48mentioning
confidence: 81%
“…There are strong indications, however, that this family has a primary role in the degradation of particulate substrates, as it includes cellulolytic species, such as R. flavefaciens and R. albus, described from the rumen (Stewart et al, 1997;Flint et al, 2008), and R. champanellensis isolated from the human large intestine (Chassard et al, 2011). The breakdown of plant fiber in the rumen is dependent on such cellulolytic microorganisms, with many other species utilizing the solubilized products (Dehority, 1991).…”
Section: Discussionmentioning
confidence: 99%